(3QSGdI aj GdcdGe Ydi Cqi GdeTOOIs ((3eMehO UObi s)
(3ChdgG (B:s
(3GdMeO ddg QGaY GdeTcdGJ Yf Chdi GdCdHGH hfGUH GdYdGeGJ Ydi Pdc ef SfI hcJGH MJi EfNaV dge hSgd eG GQGOhg aLRehG HCf GdaGYd MbjbI ef bUOhg s
(3BNQgG (B:s
(3heG Shi gPg GdUhQg JYQH Ci ajgG aUhQI GdHfGA Od YdjgG eaghe GdcdGe hUhQ GdEYQGH Od YdjgG efWhbg LYdfG Gddg HaVdg hEjGce ef GdfGWbjf HGdNjQ GdUGeJjf Yf GdZjQ hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs